2007
DOI: 10.1111/j.1550-7408.2007.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol Synthase of Tetrahymena: Inositol Isomers as Substrates in Phosphatidylinositol Biosynthesis and Headgroup Exchange Reactions

Abstract: Phosphatidylinositol (PtdIns) synthase in microsomal fractions derived from Tetrahymena vorax was studied to determine its activity requirements. The suitability of inositol isomers as substrates for the synthase and in headgroup exchange reactions also was investigated. Tetrahymena PtdIn synthase activity was optimum in the presence of 2 mM MgCl2 plus 2 mM MnCl2, a pH of 7.8, and a temperature of 30 degrees C. The enzyme retained approximately 80% of its activity after incubation at 70 degrees C for 10 min. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This reaction has been characterized in T. vorax microsomes, where the substrates included both myo - and non- myo -inositol isomers(Riggs et al, 2007). T. thermophila has a single PIS gene (TTHERM_00678350) whose expression profile is similar to the enzymes involved in the synthesis of inositol (MIPS and InsPase).…”
Section: Studies On Membrane Lipids In Tetrahymenamentioning
confidence: 99%
“…This reaction has been characterized in T. vorax microsomes, where the substrates included both myo - and non- myo -inositol isomers(Riggs et al, 2007). T. thermophila has a single PIS gene (TTHERM_00678350) whose expression profile is similar to the enzymes involved in the synthesis of inositol (MIPS and InsPase).…”
Section: Studies On Membrane Lipids In Tetrahymenamentioning
confidence: 99%
“…scyllo-Inositol (SI), the C-2 epimer of MI, is relatively rare but is sometimes found in plants, for example in barley seeds (Kinnard et al, 1995) and chrysanthemum buds (Ichimura et al, 2000). Also, SI is sometimes present in phosphatidylinositol, since the phosphatidylinositol synthase of Tetrahymena vorax is known to act not only on MI but also on SI (Riggs et al, 2007). In mammals, SI has been shown to localize in the kidney and brain (Sherman et al, 1968), and an enzyme from bovine brain was found to interconvert MI and SI (Hipps et al, 1976).…”
Section: Introductionmentioning
confidence: 99%